Pain management of pemphigus vulgaris - Rajesh Kumar Muniandy; Nagarajan Nagalingam; Liew, Constance Sat Lin; Voo, Michelle Sook Yee (BMJ Publishing Group, 2022)
Pemphigus is a rare autoimmune bullous disease which affects the mucous membranes and skin. Pemphigus vulgaris (PV) is the most prevalent type of pemphigus. PV presents with extremely painful, non- healing oral erosions. However, there are only a handful of reports addressing the pain management of PV. We would like to present a case of a painful PV, which was successfully managed.